PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KEPUASAN NASABAH DAN DAMPAKNYA TERHADAP LOYALITAS NASABAH PT. BANK RAKYAT INDONESIA - Yunanda Eka Putra; Mukhlis Yunus; Sulaiman Sulaiman (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACTThis study aims to determine Customer Relationship Management influence on Customer Satisfaction and its impact on Customer Loyalty of PT.Bank Rakyat Indonesia (Persero), Tbk Branch Office in Bener Meriah. The study population is all customers in in the bank numbering 13.939 customers. This study uses proportioned/stratified random sampling with a sample size of 250 respondents. The analytical method used is structural equation modeling (SEM). The results showed that the Customer Relationship Management significantly influences both on satisfaction and its customer loyalty. Furthermore, satisfaction also affects its customer loyalty. Customer satisfaction plays a role as partially mediator between the influences of Customer Relationship Management on its Customer Loyalty. The implications of this research, the management of PT. Bank Rakyat Indonesia needs to improve its Customer Relationship Management program that can increase its customer loyalty. Keywords: Customer Relationship Management, Satisfaction, Customer Loyalty